Interactions between plastic deformation and precipitation in Aluminium alloys: A crystal plasticity model. (1st April 2023) - Bignon, Madeleine; Ma, Ziyu; Robson, Joseph D.; Shanthraj, Pratheek
Abstract: This work presents a crystal plasticity model for dynamic precipitation in aluminium alloys. It takes into account both the influence of an evolving precipitate distribution on the critical stress for dislocation glide, and the accelerating effect of deformation on precipitation kinetics. The effect of precipitates on deformation behaviour is integrated into the crystal plasticity constitutive law. The effect of deformation on precipitation kinetics is modelled spatio-temporally using a multi-class precipitation kinetic model (KWN) incorporating the effect of deformation through accelerated solute diffusion caused by the production of excess vacancies. The model is applied to growth and coarsening of shearable precipitates in pre-aged AA7075 alloy under deformation at 150°C, which corresponds to an industrially relevant production. This paper first explores the influence of dynamic precipitation on the tensile behaviour, showing that dynamic precipitation might be responsible for a gain in uniform elongation and tensile stress of respectively 2% strain and 50 MPa for the case at hand. The influence of dynamic precipitation on the development of plastic strain heterogeneities is discussed. The model demonstrates how spatial heterogeneities in precipitate distribution may develop during deformation, and how these heterogeneities correlate with the development of strain heterogeneities. The precipitate distributions obtained under static or dynamic ageing are predicted and compared with each other, and the influence of texture is discussed. Graphical abstract: